FOREIGN DIRECT INVESTMENTS IN THE ECONOMY OF UKRAINE: STATE AND FACTORS AFFECTING THE PROCESS OF THEIR ATTRACTION - HRYNCHUK, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the state and dynamics of direct foreign investment in the economy of Ukraine and identifies the most important factors influencing the process of their attraction. The study of the topic is carried out in the following logical sequence: the theoretical aspects of direct foreign investments, their role in the country’s economy are considered; the dynamics of foreign direct investments inflows into the economy of Ukraine for 2019-2023is analyzed and the reasons that had a negative impact on the volume of their investments are indicated; the main concepts related to the determinants of direct foreign investment, such as political, economic, legal and procedural determinants, are considered; factors affecting the flow of direct foreign investment into the country are highlighted; proposals for the formation of a policy of attracting foreign direct investment are provided. The study shows that the inflow of foreign direct investment mostly depends on the integrated economic situation: general political, economic and institutional and legal conditions prevailing in the host country. These factors constitute the investment climate in which the investment process takes place, and these elements cannot be separated from each other, they form a single whole. The absence of one or any other component will affect the investment decision and it is the reason for falling into the risk zone, which a direct foreign investor will face. Each determinant consists of a subset of private parameters that are specific to each country. Therefore, more accurate methods of assessing these private parameters are needed in order to quantify the level of favorableness of the integrated investment environment in the host country. The data obtained as a result of such assessments will be the basis for the formation of strategies for attracting direct foreign investment at the macro level.